Delimitation and diversity of the genus Badula Juss. (primulaceae) - rare endemic trees of the Mascarene Archipelago - Bone, Ruth Emily (Trinity College (Dublin, Ireland). Department of Botany, 2010)
The western Indian Ocean Mascarene archipelago is a trio of geologically young volcanic islands that have never been connected to a continent or continental fragments. The islands are biologically diverse, and 72% of the 885 native angiosperm species are endemic. Badula Juss. (Primulaceae) is one of the few genera currently treated as a Mascarene endemic with a distribution across all three of the Mascarene islands.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin.